Assessing the diagnostic validity of a structured psychiatric interview in a first-admission hospital sample - NORDGAARD, JULIE (Elsevier Italy, 2012)
The use of structured psychiatric interviews performed by non-clinicians is frequent for research purposes and is becoming increasingly common in clini-cal practice. The validity of such interviews has rarely been evaluated empirically. In this study of a sample of 100 diagnostically heterogeneous, first-admitted inpatients, the results of an assessment with the Structured Clinical Interview for DSM-IV (SCID), yielding a DSM-IV diagnosis and performed by a trained non-clinician, were compared with a consensus lifetime best diagnostic estimate (DSM-IV) by two experienced research clinicians, based on multiple sources of information, which included videotaped comprehensive semi-structured narrative interviews. The overall kappa agreement was 0.18. The sensitivity and specificity for the diagnosis of schizophrenia by SCID were 19% and 100%, respectively. It is concluded that structured interviews performed by non-clinicians are not recommendable for clinical work and should only be used in research with certain precautions. It is suggested that a revival of systematic theoretical and practical training in psychopathology is an obvious way forward in order to improve the validity and therapeutic utility of psychiatric diagnosis.